2016
DOI: 10.1016/j.ijpara.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two rounds of praziquantel mass drug administration on Schistosoma mansoni infection prevalence and intensity: a comparison between community wide treatment and school based treatment in western Kenya

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 34 publications
2
59
1
Order By: Relevance
“…However, it was noted that the prevalence in boys (29.3 percent) was higher than the prevalence in girls with a percentage difference of four percent. This finding did not corroborate to the study done in Nepal in which it was found that the prevalence of STH in females was higher than the prevalence in males [8]. The difference in the finding of the two studies was attributed to the fact that the study in Nepal included females and males of all age groups.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…However, it was noted that the prevalence in boys (29.3 percent) was higher than the prevalence in girls with a percentage difference of four percent. This finding did not corroborate to the study done in Nepal in which it was found that the prevalence of STH in females was higher than the prevalence in males [8]. The difference in the finding of the two studies was attributed to the fact that the study in Nepal included females and males of all age groups.…”
Section: Discussioncontrasting
confidence: 82%
“…Low prevalence of STH g pupils of upper classes compared to lower classes colleagues was attributed to two factors: maturity and learning pressure in upper value of .86262 the difference in prevalence of STH among the pupils of different classes was however, not statistically Interventions for the control and prevention of STH must therefore, among other measures, focus on health promotion and education, and must also focus on behaviour change such as encouragement of the pupils to s when outdoors, washing of hands after toilets visitation, and even washing of Based on the type Soil-Transmitted Helminthiases, it was established that infections by hookworms were the highest at 53 percent followed by roundworms at 39 percent whereas infections by whip worms were the least at only eight percent. These results were similar to the study in Nigeria, in which it was found that A. lumbricoides was the most common STH at 29.3 percent while T. trichiura had the least prevalence at 2.3 percent [4,8]. This implied that interventions for control and prevention of STH among the community as much as it should focus on all types of worms, should pay much specific attention to A. lumbricoides.…”
Section: Associated Risk Factor Of Sthsupporting
confidence: 87%
See 3 more Smart Citations